The role of social connectedness in employee mental health with self-esteem as mediator in the Jabodetabek area - Shafa Zalikha Putri; Zamralita Zamralita; Reza Fahlevi (Priviet Social Sciences Journal, 2026)
The purpose of this study was to test whether social connectedness predicts the mental health of employees in the Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek) region while treating self-esteem as a variable that might mediate the link. Participants were recruited through convenience sampling, a non-probability approach, yielding 324 workers drawn from a range of job types. The measurement relied on three tools: the Mental Health Continuum–Short Form (MHC-SF) for overall mental health, the Social Connectedness Scale–Revised (SCS-R) for the degree of connectedness, and the Rosenberg Self-Esteem Scale (RSES) for self-esteem. Analysis showed that connectedness was a significant predictor of mental health (p < .001) and likewise had a significant bearing on self-esteem (p < .001). Self-esteem, by contrast, had no association with mental health (p = .622); thus, it did not carry the relationship between connectedness and mental health. Taken together, the pattern is consistent with employees’ mental health being associated primarily with experiences of connection rather than with a self-esteem pathway. Because the design is cross-sectional and based on self-report, these results should be read as associations rather than causal effects. Building a stronger sense of belonging among staff, whether through supportive interactions, cooperative work settings, or a positive social atmosphere, therefore looks like a workable route to better mental well-being overall.